Training and testing practices of strength and conditioning coaches in Argentinian Rugby Union - Zabaloy, S.; Tondelli, E.; Pereira, L. A.; Freitas, T. T.; Loturco, I. (International Journal of Sports Science & Coaching, 2022)
The Argentine Rugby Union is a top-tier rugby nation (ranked 8th according to World Rugby), with the Buenos Aires Rugby Union being the largest competitive league. To date, the training practices of Argentinian rugby strength and conditioning coaches have not yet been documented and analyzed. We used an online survey to characterize the training and testing strategies commonly implemented by Argentinian rugby strength and conditioning coaches, which could serve as a guideline for coaching education programs. Thirty-five rugby strength and conditioning coaches (age: 42.0 ± 8.9 years; professional experience: 16.8 ± 8.3 years) working across 35 clubs (from a total of 40 clubs) participated in the study. The survey consisted of eight sections: 1) background information; 2) strength-power development; 3) speed training; 4) plyometrics; 5) flexibility training; 6) physical testing; 7) technology use; and 8) programming. Overall, Argentinian strength and conditioning coaches did not frequently use periodization strategies to structure programs, reported a progressive reduction in training loads across the season, and prescribed primarily Olympic weightlifting and squat as resistance exercises during different training periods. The analyses of speed training revealed high utilization of form-running, plyometrics, and sport-specific movements. Our results also indicated that physical testing and technology may be affected by the economic difficulties of Argentinian clubs. This study presents new information regarding the training methods adopted by Argentinian rugby strength and conditioning coaches, while providing them with new insights to improve their professional practices. Practitioners from different countries working in competitive rugby leagues can use the information provided here to examine their own practices and implement evidence-based programs for elite rugby players.